Contributing factors of critical thinking skills acquisition in sustainability of higher education: a systematic review / Norhayati Kassim, Nur Maizura Ahmad Noorhani and Siti Rasidah Md Sakip - Kassim, Norhayati; Ahmad Noorhani, Nur Maizura; Md Sakip, Siti Rasidah (2022)
Critical thinking (CT) is a key to sustainable development as it requires the graduates who can think critically in handling built environment projects. This skill is crucial while promising the good quality of decisions made in facing the real working experience. The acquisition of this skill among graduates is different from each other due to various factors such as teachers' factor, students' factor and organisations' factors. Previous studies reveal the empowerment of these skills among graduates is still at average to lower level especially built environment education. Therefore, the aim of this systematic review is to summarize the current literature in the factors that could possibly influence the CT skills among higher education including built environment education by using a systematic review. The review process includes five main methodological steps, namely guided by review protocol, formulation of research questions, systematic searching strategies based on identification, screening, and eligibility on several established databases such as Scopus, Web of Science and Science Direct, followed by quality assessment, and data extraction and analysis. The literature was obtained from three databases Web of Science, Scopus, and ScienceDirect that published articles between 2012 and 2022 on the factor contributing to the acquisition of CT development among higher education students. The review employed the thematic analysis using ATLAS.ti 8 to answer the research question. The results of this paper presented in two forms: quantitative and qualitative data. Paper revealed three main themes namely 1) students factor 2) education factors; and 3) personal factors might influence the acquisition of CT among higher education students. This paper could benefit higher education organizations in finding an alternative way in improving the development of CT skills among students. These findings have significant implications for improving graduates CT skill by improving factors and enabling focused efforts to improve these skills thus could improve the graduate's quality.